Efek latihan tungkai bawah menggunakan kursi pada kualitas tidur, kebugaran, dan risiko jatuh pada orang tua - Saputra, Adhe; Muzaffar, Ahmad (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Low physical activity levels can cause several degenerative diseases, especially for the elderly. Thus, the research objective was to examine the effects of the lower limb exercises program using a chair on sleep quality, fitness, and the risk for falls in the elderly. The experimental method with a pretest-posttest control group design approach was used in this research with a total of 20 male participants with average (age 66.85 ± 5.63 years, weight 45.75 ± 2.62, height 154.82 ± 5.18 cm, and BMI 19.16 ± 1.86). After doing lower limb exercises for eight weeks, the results showed sleep duration, fitness marked by the 6MWT test, and balance in the experimental group. There were significant differences, while there were no significant differences in the control group. Thus, hopefully, it was found in the research results that the exercise of using a chair for the elderly could help improve aerobic ability and balance. It was positively correlated with decreasing sleep duration problems in the elderly. It had the potential to reduce the risk of getting a history of other diseases that could interfere with the daily lives of the elderly.